Bioreactivity of stent material: Activation of platelets, coagulation, leukocytes and endothelial cell dysfunction in vitro. (18th August 2017) - Ollivier, Veronique; Roques, Caroline; Receveur, Nicolas; Gratz, Matthias; Feldman, Laurent; Letourneur, Didier; Gachet, Christian; Mangin, Pierre H.; Jandrot-Perrus, Martine
Abstract: Outcome of patients with coronary artery disease has been significantly improved by percutaneous coronary interventions with stent implantation. However, despite progress made on devices and antithrombotic treatments, stent thrombosis remains an important issue because of serious adverse consequences. Several mechanisms are assumed to favor stent thrombosis as platelet aggregation, fibrin formation, defective healing and local inflammation. The objective of this study was to evaluate in vitro the thrombogenicity, proinflammatory properties and healing capacities of cobalt–chromium (CoCr), an alloy commonly used for cardiovascular implants. Platelet adhesion was quantified in static and flow conditions. Thrombin generation was performed using the calibrated automated thrombogram. Neutrophil adhesion and formation of extracellular traps were visualized by scanning electron microscopy and by immunofluorescence. The phenotype of endothelial cells grown on CoCr was analyzed using specific antibodies, whereas the procoagulant potential was analyzed by measuring thrombin generation and protein C activation. Our results show that human blood platelets adhere to and are activated on CoCr in static and flow conditions. Overall, CoCr significantly induced thrombin generation in the presence or absence of platelets by 1.5- and 4.8-fold, respectively, involving activation of the contact pathway and activation of platelets. CoCr triggered leukocyte adhesion and behaved as a scaffold for the formation of neutrophil extracellular traps in the presence of platelets. Endothelial cells adhered and formed a monolayer covering CoCr. However, they switched from an anticoagulant phenotype to a procoagulant one with a significant 2.2-fold increase in thrombin generation due to a combined 30% reduced capacity to trigger protein C activation and 30% increased expression of tissue factor. Moreover, endothelial cells grown on CoCr acquired an inflammatory phenotype as indicated by the increased expression of ICAM-1 and VCAM-1. These data show that bare CoCr is prothrombotic and proinflammatory due to its capacity to activate platelets and coagulation and to induce leukocyte adhesion and activation. More importantly, even if endothelialization is achievable, the switch in endothelial phenotype prevents effective healing. Furthermore, we propose our methodology for future preclinical in vitro evaluation of the thrombogenicity of stent materials.